COVID-19: Technology, Social Connections, Loneliness, and Leisure Activities: An International Study Protocol - Marston, Hannah R.; Ivan, Loredana; Fernández-Ardèvol, Mireia; Rosales Climent, Andrea; Gómez-León, Madelin; Blanche-T, Daniel; Earle, Sarah; Ko, Pei-Chun; Colas, Sophie; Bilir, Burcu; Öztürk Çalikoglu, Halime; Arslan, Hasan; et al. (Frontiers in Sociology, 2020)
Drawn from the stress process model, the pandemic has imposed substantial stress to individual economic and mental wellbeing and has brought in unprecedented disruptions to social life. In light of social distancing measures, and in particular physical distancing because of lockdown policies, the use of digital technologies has been regarded as the alternative to maintain economic and social activities. This paper aims to describe the design and implementation of an online survey created as an urgent, international response to the COVID-19 pandemic. The online survey described here responds to the need of understanding the effects of the pandemic on social interactions/relations and to provide findings on the extent to which digital technology is being utilized by citizens across different communities and countries around the world. It also aims to analyze the association of use of digital technologies with psychological wellbeing and levels of loneliness. The data will be based on the ongoing survey (comprised of several existing and validated instruments on digital use, psychological wellbeing and loneliness), open for three months after roll out (ends by August and September) across 11 countries (Austria, France, Germany, India, Malta, Portugal, Romania, Spain, Turkey and UK). Participants include residents aged 18 years and older in the countries and snowball sampling is employed via social media platforms. We anticipate that the findings of the survey will provide useful and much needed information on the prevalence of use and intensities of digital technologies among different age groups, gender, socioeconomic groups in a comparative perspective. Moreover, we expect that the future analysis of the data collected will show that different types of digital technologies and intensities of use are associated with psychological wellbeing and loneliness. To conclude, these findings from the study are expected to bring in our understanding the role of digital technologies in affecting individual social and emotional connections during a crisis.